1994
DOI: 10.1111/j.1532-5415.1994.tb06856.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Special Care Unit for Patients with Advanced Alzheimer's Disease on Patients' Discomfort and Costs

Abstract: These results suggest that management of patients with advanced DAT on a DSCU using a palliative care philosophy may result in less patient discomfort and lower costs than management on a TLTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 23 publications
(42 reference statements)
2
86
0
Order By: Relevance
“…For residents with advanced dementia, who are facing a high 6-month mortality and the frequent necessity of restraints to prevent removal of intravenous lines, the benefi t of such aggressive care has been increasingly questioned. 3,26,[35][36][37][38][39] Our fi ndings lend further support to this position because aggressive care appeared to offer little survival benefi t in the 3 months after lower respiratory tract illness. Previous analysis of Missouri LRI Study data found no difference in 1-month mortality between residents fi rst treated in the nursing home or the hospital, after adjusting for illness severity and probability of hospitalization.…”
Section: Discussionsupporting
confidence: 52%
“…For residents with advanced dementia, who are facing a high 6-month mortality and the frequent necessity of restraints to prevent removal of intravenous lines, the benefi t of such aggressive care has been increasingly questioned. 3,26,[35][36][37][38][39] Our fi ndings lend further support to this position because aggressive care appeared to offer little survival benefi t in the 3 months after lower respiratory tract illness. Previous analysis of Missouri LRI Study data found no difference in 1-month mortality between residents fi rst treated in the nursing home or the hospital, after adjusting for illness severity and probability of hospitalization.…”
Section: Discussionsupporting
confidence: 52%
“…In the DSCU, discomfort was lower and mortality was higher. There were fewer hospitalizations and costs were lower [106].…”
Section: Research Trends In Dementia At the End Of Lifementioning
confidence: 99%
“…Prospective observational [60,89,91,95,102,106,108] and intervention studies [33,86,87,101,103,104,110] provide the best evidence on how to improve care and 14 have been completed or are ongoing (Table 1). However, most studies have been small, retrospective, or both.…”
Section: Research Trends In Dementia At the End Of Lifementioning
confidence: 99%
“…One uncontrolled trial was done in a single nursing home and compared a palliative-care approach with traditional longterm care management for persons with severe dementia. By incorporating a pain-management component, the palliative-care approach led to decreased discomfort scores, fewer transfers to acute care, and lower costs [37]. Use of the Assessment of Discomfort in Dementia (ADD) protocol, a systematic approach to pain assessment and management for nurses, ameliorated discomfort behaviors in 84 percent of enrolled residents in a convenience sample of 143 residents [38].…”
Section: Best Practices In Pain Management In Persons With Dementiamentioning
confidence: 99%